Mycetoma of the Breast: A Case Report - Meilany Durry; Lily L. Loho (Universitas Sam Ratulangi, 2023)
Abstract: Mycetoma is a chronic suppurative infection affecting skin, subcutaneous tissue, and bones which is common in tropical and subtropical regions. The manifestations of mycetoma are painless subcutaneous mass, multiple sinuses and purulent or seropurulent discharge that may contain grains. We reported a case of a 39-year-old female with a complaint of skin mass with discharge in her left breast for about a year. The clinical diagnosis was a breast tumour with suspicion of malignancy. A histopathological examination of the breast biopsy was performed which showed foci of granulomas consisting of chronic inflammatory cells, foamy macrophages, and many multinucleated cells. In several granulomas, there were eosinophilic masses with hypha in the peripheral and arranged radially. In conclusion, based on clinical and histopahological examinations the diagnosis of this case was a mycetoma of the breast. Keywords: mycetoma; breast; deep mycosis; mammary infection; pathological diagnosis